2002
DOI: 10.4049/jimmunol.169.2.1021
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Express Functional IL-13 in Eosinophilic Inflammatory Diseases

Abstract: IL-13 is an immunoregulatory and effector cytokine in allergic diseases such as bronchial asthma. A variety of immune and non-immune cells are known as IL-13 producers. In this study we investigated whether and under what conditions human eosinophils generate IL-13. Freshly isolated highly purified peripheral blood eosinophils from patients with several eosinophilic inflammatory diseases and from normal control individuals were investigated. We observed that blood eosinophils from patients suffering from bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(155 citation statements)
references
References 47 publications
3
151
1
Order By: Relevance
“…As shown in previous studies examining lung injury, we found that reduced eosinophils and thus remodeling mediators, including fibronectin, led to a partial reversal of ileal inflammation and remodeling. 19,25,28,29 Eosinophils are well-known sources of functional IL-13, 43 a molecule associated with remodeling and fibrosis. 44 For instance, a number of studies have highlighted the role of IL-13 as a central mediator driving the major asthmatic pathologies, including eosinophilia, mucus accumulation, fibrosis, and airway hyperresponsiveness.…”
Section: E: Cd8mentioning
confidence: 99%
“…As shown in previous studies examining lung injury, we found that reduced eosinophils and thus remodeling mediators, including fibronectin, led to a partial reversal of ileal inflammation and remodeling. 19,25,28,29 Eosinophils are well-known sources of functional IL-13, 43 a molecule associated with remodeling and fibrosis. 44 For instance, a number of studies have highlighted the role of IL-13 as a central mediator driving the major asthmatic pathologies, including eosinophilia, mucus accumulation, fibrosis, and airway hyperresponsiveness.…”
Section: E: Cd8mentioning
confidence: 99%
“…Other eosinophil-derived and stored cytokines [e.g. IL-4 (23), IL-13 (24,25)] and chemokines [e.g. RANTES (26,27)] may further amplify the inflammatory milieu.…”
Section: Eosinophil Production and Survival Within Tissuesmentioning
confidence: 99%
“…Although many of these cytokines are produced by lymphocytes, reports have demonstrated the ability of eosinophils to synthesize, store and secrete an array of cytokines [e.g. IL-4 (66, 67) and IL-13 (24,25)] and chemokines [e.g. RANTES (68)].…”
Section: Eosinophil Modulation Of Tissue Inflammationmentioning
confidence: 99%
“…Blood and tissue eosinophils are terminally differentiated cells and therefore have a limited capacity to synthesize new proteins. However, based on results from multiple studies, it is now clear that eosinophils generate a wide spectrum of inflammatory and regulatory cytokines, such as TNF, TGF, GM-CSF, IL-4, IL-5, IL-8, and IL-13 (8,9). Some of these peptide mediators, such as TNF, act as amplifiers in inflammatory reactions with the risk of enhancing tissue damage.…”
Section: A Straumannmentioning
confidence: 99%